Coordenadas de la política de seguridad española : análisis y sugerencias - Viñas, Angel (Estudios Internacionales, 1985)
Security policy is a modern extension of defense policy. To the latter it incorporates an incessant search for the most convenient strategies and actions to resolve interstate conflicts without the application, in any way, of military means. In the Spanish case, the controversy over security policy has focused almost exclusively on the issue of whether or not Spain will join the North Atlantic Treaty Organization (NATO). Scientific treatment of the issue has, however, been conspicuous by its absence. This work presents the most pressing problems that affect European and Spanish security policy at the present time, as well as the state of the issue from the perspective of the open debate in Spain over the last few years.